الجملة الإنشائية في اللغتين العربية والإندونيسية في ضوء التحليل التقابلي (جملة النهي مثالاً): Comparative Study of Arabic and Indonesian in Prohibition Sentences - Rustam Koly (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2022)
This study aims to determine Arabic and Indonesian grammar in the form of prohibition sentences, by discussing the similarities and differences between them, after describing their respective grammars to find out where the difficulties of Indonesian students in learning Arabic, especially in prohibition sentences. This study uses a comparative research methodology through three research steps, namely: (1) to describe prohibited sentences in Arabic and Indonesian grammar; (2) collect the similarities and differences in the prohibition sentences in Arabic and Indonesian grammar; (3) predicting the difficulties of students in learning Arabic due to grammatical differences between Arabic and Indonesian. The results of this study indicate that the two languages ​​have similarities in: 1) prohibition and its era, where the prohibition sentence in both languages ​​is addressed to the interlocutor, for the present or future time; 2) the prohibition sentence using only one tool